Educational videos to raise awareness of risks and transmission of antimicrobial resistance (AMR) and intersection with livestock for Kenya - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The videos are available on YouTube and were promoted very extensively through WhatsApp. The Government of Kenya have been using the videos in public message campaigns (e.g., televised in waiting rooms of public hospitals). They have recently been endorsed as part of national training activities for antimicrobial resistance (AMR).